Clinical profile and management of vitreous hemorrhage in tertiary eye care centre in Nepal - Manandhar, Laxmi Devi; Thapa, Raba; Poudyal, Govinda (Nepalese Journal of Ophthalmology, 2020)
Introduction: Vitreous hemorrhage is one of the most common diseases presenting to emergency department and leading cause of painless vision loss. Objectives: To determine the profile of vitreous hemorrhage in patients presented to Outpatient Department (OPD) and emergency Department of Tilganga Institute of Ophthalmology (TIO). Materials and methods: This is a hospital based observational non interventional descriptive study. Total 198 patients were enrolled who visited OPD and Emergency department of TIO from August 1st 2012 to July 30th 2013. Result: Total 198 patients (201 eyes) were enrolled for the study, out of which 144 were male and 54 females. 195 were unilateral and 3 bilateral cases. Most common age group of presentation of vitreous hemorrhage was 51-60 years (24.75%). Most common presenting complaint was sudden onset of decreased vision (95%). Most common etiology of vitreous hemorrhage was branch retinal vein occlusion (22.38%). Among the total subjects, 57.7% of the patient were managed with medical therapy, 35.8% surgically and 6.47 % with combined medical and surgical treatment. Conclusion: Branch retinal vein occlusion (BRVO) is the most common cause of vitreous hemorrhage. Diabetes and hypertension are the most commonly associated systemic illnesses.